Answer: 0.0001408
Step-by-step explanation:
Get unknowns on one side and know on other side.
Divide both sides by -2
X= -7
Answer:
Step-by-step explanation:
you have to have a quadratic equation, not sure what your question is,
Substitute y = 3x + 15 to the equation -4x + 7y = 20:
-4x + 7(3x + 15) = 20 <em>use distributive property</em>
-4x + (7)(3x) + (7)(15) = 20
-4x + 21x + 105 = 20 <em>subtract 105 from both sides</em>
17x = -85 <em>divide both sides by 17</em>
x = -5
Substitute the value of x to the equation y = 3x + 15:
y = 3(-5) + 15
y = -15 + 15
y = 0
<h3>Answer: x = -5 and y = 0</h3>